EEG Frequency and Phase Coupling during Human Information Processing - Schack, B.; Rappelsberger, P.; Vath, N.; Weiss, S.; Möller, E.; Grießbach, G.; Witte, H. (Methods of Information in Medicine, 2001)
Neuronal activity during information processing is represented by oscillations within local or widespread neuronal networks. These oscillations may be recorded by the EEG (electroencephalogram). The oscillatory interaction between neuronal ensembles may be at one single frequency or at different frequencies due to non-linear coupling. The investigation of momentary coherence and phase enables the examination of synchronized oscillatory network activity during fast-changing cognitive processes. On this basis information transfer from occipital areas towards frontal areas could be described during processing of visual presented words. Non-linear phase coupling between oscillations with different frequencies during memory processing was detected by means of cross-bicoherence.
Keywords: EEG (Electroencephalogram); Phase Coupling; Coherence and Phase; Bispectral Analysis; Information Processing